Effect of intradialytic mindfulness-based meditation on spiritual well-being and anxiety in hemodialysis patients: a randomized controlled trial - Murwani, Wara Gati; Fahrun Nur Rosyid; Dian Hudiyawati (Universitas Muhammadiyah Purwokerto, 2026)
Background: Patients undergoing hemodialysis frequently experience anxiety and reduced spiritual well-being; however, few studies have simultaneously addressed these outcomes using structured mindfulness-based interventions delivered during dialysis sessions. Purpose: To evaluate the effectiveness of intradialytic mindfulness-based meditation in reducing anxiety and improving spiritual well-being among patients undergoing hemodialysis. Methods: A randomized controlled trial was conducted involving 58 patients undergoing routine hemodialysis, randomly assigned to an intervention group (n = 29) or a control group (n = 29). The intervention group received a 2.5-hour mindfulness training session followed by audio-guided mindfulness practice during the first 15 minutes of hemodialysis sessions, twice weekly for four weeks. The control group rested quietly without guided practice. Anxiety was measured using the Zung Self-Rating Anxiety Scale (ZSAS), and spiritual well-being was assessed using the Spiritual Well-Being Scale (SWBS). Data were analyzed using paired and independent t-tests. Results: The intervention group showed a significant increase in spiritual well-being scores (mean change +6.07) compared with the control group (+1.21) (p = 0.021). Anxiety scores significantly decreased in the intervention group (−11.76) compared with minimal change in the control group (+0.69) (p = 0.001). The between-group effect sizes were large (SWB: d = 1.36; anxiety: d = −1.88). Conclusion: Intradialytic mindfulness-based meditation is a feasible and effective complementary intervention that improves spiritual well-being and reduces anxiety among patients undergoing hemodialysis.